Parent-Teacher Conference as a Rhetorical Challenge in Educational Practice - Vignjević, Jelena; Pavlović Pintarić, Marina (Revija za elementarno izobraževanje, 2023)
This paper analyses educator’s communication skills during parent-teacher conferences in kindergarten. We researched the way educators communicate during twelve parent-teacher conferences in various kindergartens. In accordance with the methodology of qualitative research, chosen elements of educator’s communication during the parent-teacher conferences were observed and recorded. Results showed that observed parent-teacher conferences are well-prepared, structured, substantially suitable and interactive, with apt vocabulary and elements of eloquence. The greatest shortcoming of the educator’s communication was an underdeveloped active listening technique. Moreover, there were obvious differences in individual communication skills of the educators. The results of this research can serve as a tool for contemplating pedagogical practice in early childhood education.
Keywords: educator’s communication skills, parent-teacher conference, rhetorical skills